Improving year 4 pupils sight words recognition in spelling by using let's spell it right (lespir) digital spelling application / Muhammad Zulharraz Zulkhairy ... [et al.] - Zulkhairy, Muhammad Zulharraz; Zawawi, Wan Najmi Zafri; Mohd Pisol, Muhammad Faheem Azfar; Mohd Salehuddin, A’isy Sofyan; Setapa, Mohd Saharudin (2020)
Let's Spell It Right (LeSPIR) Digital Spelling Application is an innovation on enhancing year 4 pupils sight words recognition as a way of improving pupils' skill in spelling. Most pupils tend to misspell words during spelling activity. Misspelling of words occurs because pupils did not recognize the words spelling structure or also known as orthography. This innovation aimed to identify the effectiveness of LeSPIR and pupils' interest in using LeSPIR. Participants are required to use the application by spelling different words by arranging letters correctly throughout the action. The words used in the application are selected from the common words in the textbook and are listed according to different categories. Pupils also used the dictionary, audio and quiz which is built in with the application to help them complete the spelling. After four times using LeSPIR, participants were able to spell words correctly by recognizing its spelling structure and they enjoyed using the game. Overall, the impact of using LeSPIR enabled pupils to reduce errors in spelling. For further improvement, it is suggested that pictures can be used when introducing words to pupils so that the spelling structure of those words can be recognized accurately.